Droplet wetting and evaporation : from pure to complex fluids - Brutin, David (Academic Press is an imprint of Elsevier, 2015)
Droplet Wetting and Evaporation provides engineers, students, and researchers with the first comprehensive guide to the theory and applications of droplet wetting and evaporation. Beginning with a relevant theoretical background, the book moves on to consider specific aspects, including heat transfer, flow instabilities, and the drying of complex fluid droplets. Each chapter covers the principles of the subject, addressing corresponding practical issues and problems. The text is ideal for a broad range of domains, from aerospace and materials, to biomedical applications, comprehensively relaying the challenges and approaches from the different communities leading the way in droplet research and development.